Morphological and Physiological Responses in Red Amaranthus (Amaranthus tricolor L.) and Green Amaranthus (Amaranthus dubius Mart. ex Thell.) Under Progressive Water Stress - Amma, Chithra Santhakumari; Rajalakshmi, Radhakrishnan (Asian Journal of Biological and Life Sciences)
Aim: Drought is a major constraint to the sustainable production of crop plants around the globe. Amaranthus tricolor (var. Arun) and Amaranthus dubius (var. CO1) are the leafy vegetables commonly cultivated in India, especially in Kerala. To date, the morphological and physiological changes with respect to drought stress and its mechanisms are not known thoroughly. Materials and Methods: The current research attempted to instigate the morphological and physiological changes of two Amaranth varieties under drought stress. The plant varieties were subjected to different levels of soil water treatments such as mild (4 days), moderate (6 days), and severe (8 days) stress, along with the control. After 15 days of transplanting, the water supply was limited to impose stress. Results: Morphological responses showed that only severe stress inhibited Amaranthus growth. Therefore, the stress at different stages of growth can reduce yield possessing a threat to agronomic activity. Even though there was a visible morphological change, the plants physiologically adjust the water stress condition by increasing their relative water content, decrease in electrolyte leakage, and chlorophyll stability index. The results also showed that the green variety was more tolerant than the red, even in severe water stress conditions. Conclusion: The present study helps in the future crop improvement programme of the green leafy vegetable, Amaranth.
Keywords: A. dubius; Amaranthus tricolor; Electrolyte leakage; Leaf area; Relative water content; Water stress